Terapia fotodinâmica para o tratamento de leishmaniose tegumentar americana : avaliação da associação de terapias em camundongos experimentalmente infectados com Leishmania (Leishmania) amazonensis - Volpe, Roberta Ayres Ferreira do Nascimento (2017)
American cutaneous leishmaniasis (ACL) is an infectious disease caused by protozoan parasites of the genus Leishmania that affects the skin and mucous. There are three main clinical forms of the disease: cutaneous leishmaniasis, mucocutaneous leishmaniasis and diffuse cutaneous. Cutaneous leishmaniasis is the most common form, accounting for over 90% of cases in Brazil. Currently available drugs for treatment are injectable, with side effects, long-term treatment regimen and the possibility of drug resistance. Thus, alternative therapies have been tested, including photodynamic therapy. To assess the effectiveness of photodynamic therapy on its own and associated with drugs prescribed for the treatment of ACL. BALB/c mice were experimentally infected with Leishmania amazonensis and divided into 6 groups: Gluc+PDT treated with Glucantime® and photodynamic therapy with methylene blue/red LED (light-emitting diode); Gluc treated with Glucantime®; PDT treated with photodynamic therapy with methylene blue/red LED; Ampho+PDT treated with Amphotericin and photodynamic therapy with methylene blue/red LED; Ampho treated with Amphotericin and Control which were infected but not treated. Two treatment cycles were performed. The first between 45 and 75 days after the infection, with the LED devices 4 cm apart from the lesion, applied twice weekly for 4 weeks. A second cycle was performed between 105 and 135 days after the infection with the LED devices 1 cm away from the lesion, 3 times a week for 4 weeks. After 165 days of infection, the parasite load was determined. At the end of the first and second treatment cycles, there were no statistically significant differences (p> 0.05) between measures of volume and thickness of the infected footpads in the treated groups when compared with the control group. However, there was a significant reduction (p <0.05) in the parasitic load of the popliteal lymph node of the Gluc+PDT, Gluc, PDT and Ampho groups when compared with the control group (p> 0.05). Findings: The results showed that although there is no significant difference in the evaluations of footpad size (thickness and volume), there is a downward trend of measurements in the group Gluc+PDT, as can be observed by volume data and by parasite load negative.